Geocoding and Development of a Web-Based Water Distribution Geospatial Information System for Ilorin Metropolitan City, Kwara State Nigeria - Amoo, Oseni Taiwo; Salami, Habib Adedayo; Okeola, Olayinka Gafar; Sunday, Abayomi; Abdulkadir, Taofeeq Sholagberu; Salami, Adebayo Wahab (Universitas Sanata Dharma, 2025)
Water is essential for human life and activities, but its supply depends on the proximity and interconnection network with the populations or cities that need it. Moreso, the proper functioning of water supply systems (WSS) relies on the expertise and experience of field workers who rely on information from maps or field surveys, whose processes and mapping methods are labour-intensive, time-consuming, and are done relatively infrequently. This study explores modern spatial databases for meaningful technical progress using the Quantum Geographic information system (QGIS) server to host a web-based geocoding platform to view the production, transmission, and delivery of drinking water from the source to household users according to the capacities planned for by WSS. The resultant results met expert expectations on the designed web system and showed information on pipe network, road connection, drinking water distribution layout, catchment boundary, slope, and sub-catchment geometric properties demonstrating the utility of a web-based online Map plugin in the GIS environment as a data management, scenario analysis, and decision support tool in managing water infrastructure for an expanding metropolitan city like Ilorin, Kwara State.